Comparative results of repair of Ischemic Mitral Regurgitation (IMR): Conventional against Trans-Septal Approach - Memon, Ahson; Ansari, Junaid; Khan, Ghufranullah; Shah, Ali; Aziz, Peer Asad; Ali, Hamid (International Journal of Endorsing Health Science Research, 2017)
Objective: Ischemic mitral regurgitation is common and increases mortality, even when mild. (American Heart Association) AHA and European association have both stressed the need of mitral valve repair in patients with moderate or more regurgitation. The aim of this study was to compare the results with the conventional and right atrial trans-septal approach of mitral valve repair in Ischemic Mitral Regurgitation (IMR). Methodology: A total of 308 consecutive patients underwent mitral valve repair for IMR, between January 2012 and December 2013 at Tabba Heart Institute. Patients who had at least moderate mitral regurgitation or more mitral regurgitation underwent mitral regurgitation repair. The final decision of mitral valve repair was taken after the intra operative trans-esophageal echocardiography (TEE). Results: Total number of patients included in study was222, out of those 153 (69.9%) patients underwent conventional approach and 69 (31.1) patients underwent trans-septal approach. Total 88.2% patients got off bypass in normal sinus rhythm in conventional approach group, as compared to 82.1% in trans-septal group. 11.8% and 17.9% patients got off by pass on pacing in conventional and trans-septal approach respectively. 3 patients developed junctional rhythm and 5 patients developed complete heart block in post-operative period in trans-septal approach. Conclusion: Right Atrial Trans-septal technique is a good alternative approach that can be used in relatively small atria. It not only provides an excellent exposure to the mitral valve, there also seems to be no associated rhythm disturbances encountered as well.